Aggregation-induced emission glycyrrhizic acid nanoparticles as well as preparation method and application thereof

Through the supramolecular co-assembly of glycyrrhizic acid, berberine and tannin, water-soluble aggregation-induced luminescent nanoparticles were prepared, which solved the problems of poor water solubility and low biocompatibility of AIE materials, and achieved efficient cell imaging and delivery of vectors. Trace.

CN119391404APending Publication Date: 2025-02-07SOUTH CHINA UNIV OF TECH

Patent Information

Application Number
CN202411477986.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The poor water solubility and low biocompatibility of existing AIE materials limit their application in the field of biomedicine, especially the potential for oral delivery vehicle tracing.

Method used

Through the principle of supramolecular co-assembly, three natural small molecules of glycyrrhizic acid, berberine and tannin are used to form water-soluble aggregation-induced luminescent nanoparticles. The preparation method includes adjusting the pH value of the composite solution to acidity and stirring to obtain nanoparticles. .

Benefits of technology

The prepared nanoparticles have high biocompatibility, good water solubility, strong aggregation-induced luminescence characteristics and pH fluorescence response, and can maintain stable fluorescence characteristics during gastrointestinal digestion. They are suitable for cell imaging and delivery of vectors. trace.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391404A_ABST
    Figure CN119391404A_ABST
Patent Text Reader

Abstract

The invention discloses aggregation-induced emission glycyrrhizic acid nanoparticles as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing glycyrrhizic acid or a glycyrrhizic acid derivative solution, berberine or a berberine derivative solution and a tannic acid solution to obtain a composite solution, adjusting the pH value of the composite solution to be acidic, and stirring to obtain the aggregation-induced emission glycyrrhizic acid nanoparticles. The nanoparticles are high in biocompatibility, have aggregation-induced emission characteristics and pH fluorescence responsiveness, and still show fluorescence characteristics after being digested by gastrointestinal tracts; the fluorescent probe can be used for efficient cell imaging and gastrointestinal tract fluorescence tracing, and has potential practical application value in the fields of functional food, biological medicine and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fluorescent biomaterials, and in particular relates to aggregation-induced luminescent glycyrrhizic acid nanoparticles and a preparation method and application thereof. Background Art

[0002] Fluorescent materials, including carbon quantum dots, organic dyes, fluorescent proteins, and fluorescent nanoparticles, have attracted the interest of researchers in recent years due to their excellent performance in drug delivery, biosensing, and especially bioimaging. The concept of aggregation-induced emission (AIE) reveals that specific molecules can exhibit stronger luminescence in an aggregated state than monomers in dilute solutions, effectively overcoming the aggregation-caused quenching (ACQ) effect that is common in traditional fluorescent nanomaterials. The key to the AIE phenomenon lies in the ingenious design of the molecular structure, which limits intramolecular rotation and non-radiative attenuation pathways when the molecules aggregate, thereby increasing the probability of radiative attenuation and achieving fluorescence enhancement. In the past few decades, researchers have conducted in-depth exploration and application of AIE materials. Invention patent CN 114656502 A reports a class of water-soluble AIE photosensitizers and their preparation methods. Photosensitizers LOCK-0, LOCK-1 and LOCK-2 were synthesized through a series of organic reactions. This class of aggregation-induced luminescence photosensitizers exhibits typical aggregation-induced luminescence properties, among which LOCK-2 has a fluorescence quantum yield of 56.8% in tetrahydrofuran / water (THF fraction = 99%) solution, which is higher than most reported aggregation-induced luminescence photosensitizers. However, although the photosensitizer can emit strong light in tetrahydrofuran / water (THF fraction = 99%) solution, showing typical AIE characteristics, the fluorescence phenomenon in aqueous solution almost disappears, limiting its further application potential.

[0003] In the field of biomedicine, the dynamic transport process of AIE nanomedicine in vivo can be monitored in real time through fluorescence imaging technology. This method helps to obtain information about its fate in vivo, such as structural evolution under physiological conditions, release and absorption of functional factors, and the correlation between the two, which is of great significance for accurately grasping the behavioral trajectory and mechanism of action of nanomedicine in vivo. As a simple and efficient means, supramolecular assembly has been widely used in the construction of AIE materials. It mainly constructs molecular systems with specific structures and functions through non-covalent bond forces such as hydrogen bonds, electrostatics, hydrophobicity and π-π interactions, which can significantly reduce the difficulty, cost and workload of material preparation. Invention patent CN 113788795B reports an AIE nanoparticle self-assembled from a single amphiphilic compound, which has good water solubility and fluorescence properties, but its synthesis process is complicated, and the self-assembly process requires the auxiliary dissolution of organic solvents, which poses a potential risk to biological applications. In addition, AIE nanomedicines are currently mainly administered by intravenous injection, because oral drugs are subject to the strong acidic environment of the stomach and the influence of digestive enzymes, inducing problems such as aggregation and degradation of nanomedicines. Compared with injection, oral administration not only reduces pain and infection risk, but also does not require professional operation, making it convenient for self-administration. Therefore, an AIE nano-delivery system that can effectively adapt to gastrointestinal pH changes and has high biocompatibility needs further exploration. Summary of the invention

[0004] In view of the shortcomings of the prior art, the first purpose of the present invention is to provide an aggregation-induced luminescence glycyrrhizic acid nanoparticle and a preparation method and application thereof.

[0005] The second purpose of the present invention is to solve the problems of poor water solubility and low biocompatibility of existing AIE materials, and to provide a water-soluble aggregation-induced luminescence nanoparticle formed by co-assembly of glycyrrhizic acid and other natural small molecules, and its preparation method and application for achieving oral delivery carrier tracing. The nanoparticle has high biocompatibility, good water solubility, high AIE characteristics and pH fluorescence responsiveness, and exhibits stable fluorescence characteristics during gastrointestinal digestion. The preparation process is green and mild, and can be used for efficient cell imaging, showing potential application value in constructing a delivery carrier with in vitro and in vivo visual tracing capabilities.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing aggregation-induced luminescence glycyrrhizic acid nanoparticles comprises the following steps:

[0008] The glycyrrhizic acid or glycyrrhizic acid derivative solution, berberine or berberine derivative solution and tannic acid solution are mixed to obtain a composite solution, the pH value of the composite solution is adjusted to acidic, and the composite solution is stirred to obtain aggregation-induced luminescent glycyrrhizic acid nanoparticles.

[0009] The nanoparticles prepared by the present invention have aggregation-induced emission characteristics; the AIE nanoparticles can also exhibit fluorescence characteristics during gastrointestinal digestion and have pH fluorescence responsiveness; the nanoparticles have good biocompatibility and can achieve cell imaging in Caco-2 cells.

[0010] Preferably, the mass ratio of glycyrrhizic acid or glycyrrhizic acid derivatives to berberine or berberine derivatives in the composite solution is 0.5-2:1.

[0011] Preferably, the mass ratio of tannic acid, berberine or berberine derivatives in the composite solution is 0.5-2:1.

[0012] Preferably, in the composite solution, the mass volume concentration of glycyrrhizic acid or glycyrrhizic acid derivatives is 0.01-2%, g / mL; the mass volume concentration of berberine or berberine derivatives is 0.01-2%, g / mL; and the mass volume concentration of tannic acid is 0.01-2%, g / mL.

[0013] Preferably, the mass ratio of glycyrrhizic acid or glycyrrhizic acid derivatives to berberine or berberine derivatives in the composite solution is 1.8-2.2:1; the nanoparticles prepared under this condition have good water solubility, and the particle size range of the nanoparticles is 300-400nm.

[0014] Further preferably, the mass ratio of glycyrrhizic acid or glycyrrhizic acid derivatives to berberine or berberine derivatives in the composite solution is 2:1;

[0015] Preferably, the mass ratio of tannic acid, berberine or berberine derivative in the composite solution is 1-2:1.

[0016] Preferably, the pH value is 3.5-5;

[0017] Preferably, the stirring time is 30-120 min, and the stirring speed is 100-1000 rpm;

[0018] Preferably, the mixing order includes sequentially adding tannic acid solution and berberine or berberine derivative solution to glycyrrhizic acid or glycyrrhizic acid derivative solution, sequentially adding berberine or berberine derivative solution and tannic acid solution to glycyrrhizic acid or glycyrrhizic acid derivative solution, sequentially adding glycyrrhizic acid or glycyrrhizic acid derivative solution and tannic acid solution to berberine or berberine derivative solution, sequentially adding tannic acid solution and glycyrrhizic acid or glycyrrhizic acid derivative solution to berberine or berberine derivative solution, sequentially adding berberine or berberine derivative solution and glycyrrhizic acid or glycyrrhizic acid derivative solution to tannic acid solution, and sequentially adding glycyrrhizic acid or glycyrrhizic acid derivative solution and berberine or berberine derivative solution to tannic acid solution.

[0019] Preferably, (1) the glycyrrhizic acid or glycyrrhizic acid derivative solution is prepared as follows:

[0020] Evenly dispersing glycyrrhizic acid or a glycyrrhizic acid derivative in water, and heating and stirring to obtain a solution of glycyrrhizic acid or a glycyrrhizic acid derivative;

[0021] (2) The preparation of berberine or berberine derivative solution is as follows:

[0022] Dispersing berberine or a berberine derivative in water, and heating and stirring to obtain a berberine or a berberine derivative solution;

[0023] (3) The tannic acid solution is prepared as follows:

[0024] Dispersing tannic acid in water, heating and stirring to obtain a tannic acid solution;

[0025] Preferably, the glycyrrhizic acid derivatives described in step (1) include one or more of ammonium glycyrrhizinate, monopotassium glycyrrhizinate, dipotassium glycyrrhizinate, and trisodium glycyrrhizinate; the mass volume concentration of the glycyrrhizic acid or glycyrrhizic acid derivative solution described in step (1) is 0.4-4%, g / mL;

[0026] Preferably, the heating and stirring temperature in step (1) is 60-90° C., the heating and stirring time is 5-30 min, and the heating and stirring speed is 100-1000 rpm;

[0027] Preferably, the berberine derivative described in step (2) includes one or more of berberine hydrochloride, berberine sulfate, berberine hydrogen sulfate, berberine chloride dihydrate, and 13-hydroxy-8-oxoberberine; the mass volume concentration of the berberine or berberine derivative solution described in step (2) is 0.4-2%, g / mL;

[0028] Preferably, the heating and stirring temperature in step (2) is 20-60° C., the heating and stirring time is 5-30 min, and the heating and stirring speed is 100-1000 rpm;

[0029] Preferably, the mass volume concentration of the tannic acid solution in step (3) is 0.4-2%, g / mL;

[0030] Preferably, the heating and stirring temperature in step (3) is 20-60° C., the heating and stirring time is 5-30 min, and the heating and stirring speed is 100-1000 rpm.

[0031] The aggregation-induced luminescence glycyrrhizic acid nanoparticles prepared by the above preparation method.

[0032] The above-mentioned aggregation-induced luminescence glycyrrhizic acid nanoparticles are used in the preparation of imaging agents, the preparation of tracing agents, and as drug carriers. The aggregation-induced luminescence glycyrrhizic acid nanoparticles of the present invention are used for tracing and imaging in vivo and in vitro.

[0033] Compared with the prior art, the present invention has the following advantages and beneficial technical effects:

[0034] 1) The present invention utilizes the supramolecular co-assembly principle and constructs a nanoparticle with aggregation-induced emission properties using three natural small molecules of glycyrrhizic acid, berberine and tannic acid, which can emit bright green fluorescence in aqueous solution.

[0035] 2) When the mass ratio of glycyrrhizic acid to berberine is about 2:1, the formed nanoparticles can be evenly and stably dispersed in water, which helps them enter the cell through the endocytosis pathway on the cell membrane.

[0036] 3) The raw materials used in the present invention are all natural active substances, which have the advantages of wide sources, high biocompatibility, green and renewable, and soluble in water.

[0037] 4) The preparation method of the present invention is simple, mild, green and safe, convenient and rapid, and easy to mass produce.

[0038] 5) The water-soluble aggregation-induced luminescence glycyrrhizic acid nanoparticles prepared by the present invention still have fluorescence properties during gastrointestinal digestion and show pH fluorescence responsiveness.

[0039] 6) The water-soluble aggregation-induced luminescence glycyrrhizic acid nanoparticles prepared by the present invention have good biocompatibility, can be imaged in Caco-2 cells, and have application potential in cell and biological imaging, visualized drug delivery and therapeutic systems, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is the particle size distribution diagram of nanoparticles 4 in Example 2.

[0041] Figure 2 These are fluorescence spectra of Comparative Examples 1-3, Comparative Examples 5-6, nanoparticle 4 in Example 2, and nanoparticle 9 in Example 3.

[0042] Figure 3 This is the fluorescence spectrum of nanoparticles 13-18 in Example 5.

[0043] Figure 4 This is the pH fluorescence response intensity diagram of nanoparticles 19 in Example 6.

[0044] Figure 5 This is a fluorescence intensity diagram of nanoparticles 9 in Example 3 during gastrointestinal digestion.

[0045] Figure 6 This is the Caco-2 cell imaging image of nanoparticle 4 in Example 2. DETAILED DESCRIPTION

[0046] In order to better understand the technical solutions in the present invention, the implementation scheme of the present application will be described in detail below in conjunction with examples, but the implementation scheme of the present invention is not limited thereto.

[0047] In the following examples, w / v refers to mass volume concentration, and the unit is g / mL.

[0048] Example 1

[0049] A water-soluble aggregation-induced luminescence glycyrrhizic acid nanoparticle, the preparation method of which comprises the following steps:

[0050] (1) Trisodium glycyrrhizinate powder was uniformly dispersed in deionized water, and stirred at 100 rpm for 20 min in a water bath (80° C.) to obtain a trisodium glycyrrhizinate solution with a concentration of 2% (w / v).

[0051] (2) The berberine hydrochloride powder was evenly dispersed in deionized water, and stirred at 1000 rpm for 30 min at 60° C. to obtain a berberine hydrochloride solution with a concentration of 0.4% (w / v).

[0052] (3) Dissolve tannic acid powder in deionized water and stir at 500 rpm for 30 min at 40° C. to obtain a tannic acid solution with a concentration of 1% (w / v).

[0053] (4) The berberine hydrochloride solution obtained in step (2) and the trisodium glycyrrhizinate solution obtained in step (1) are sequentially added dropwise to the tannic acid solution obtained in step (3) to obtain a composite solution, wherein the concentration of trisodium glycyrrhizinate in the composite solution is 0.2% (w / v), the concentration of berberine hydrochloride is 0.2% (w / v), and the concentration of tannic acid is 0.1% (w / v), 0.2% (w / v), and 0.4% (w / v), respectively. The pH is then adjusted to 4, and the mixture is stirred at 1000 rpm for 30 min to obtain water-soluble aggregation-induced luminescence glycyrrhizic acid nanoparticles. The nanoparticles obtained in this example are named nanoparticle 1, nanoparticle 2, and nanoparticle 3 in order from low to high concentrations of tannic acid.

[0054] Example 2

[0055] (1) The ammonium glycyrrhizinate powder was uniformly dispersed in deionized water, and stirred at 500 rpm for 5 min in a water bath (90° C.) to obtain an ammonium glycyrrhizinate solution with a concentration of 4% (w / v).

[0056] (2) The berberine sulfate powder was evenly dispersed in deionized water, and stirred at 100 rpm for 5 min at 60° C. to obtain a berberine sulfate solution with a concentration of 2% (w / v).

[0057] (3) Dissolve tannic acid powder in deionized water and stir at 60° C. and 500 rpm for 30 min to obtain a tannic acid solution with a concentration of 2% (w / v).

[0058] (4) The tannic acid solution obtained in step (3) and the berberine sulfate solution obtained in step (2) are sequentially added dropwise to the ammonium glycyrrhizic acid solution obtained in step (1) to obtain a composite solution, wherein the concentration of ammonium glycyrrhizic acid in the composite solution is 0.5% (w / v), the concentration of tannic acid is 0.5% (w / v), and the concentration of berberine sulfate is 0.25% (w / v), 0.5% (w / v), and 1% (w / v), respectively. The pH is then adjusted to 4.5, and the mixture is stirred at a speed of 500 rpm for 60 min to obtain water-soluble aggregation-induced luminescence glycyrrhizic acid nanoparticles. The nanoparticles obtained in this example are named nanoparticle 4, nanoparticle 5, and nanoparticle 6 in order from low to high concentrations of berberine sulfate.

[0059] Example 3

[0060] (1) Dipotassium glycyrrhizinate powder was uniformly dispersed in deionized water, and stirred at 300 rpm for 5 min in a water bath (60° C.) to obtain a dipotassium glycyrrhizinate solution with a concentration of 3% (w / v).

[0061] (2) The berberine bisulfate powder was evenly dispersed in deionized water, and stirred at 500 rpm for 30 min at 40° C. to obtain a berberine bisulfate solution with a concentration of 2% (w / v).

[0062] (3) Dissolve tannic acid powder in deionized water and stir at 500 rpm for 20 min at 30° C. to obtain a tannic acid solution with a concentration of 2% (w / v).

[0063] (4) The tannic acid solution obtained in step (3) and the dipotassium glycyrrhizinate solution obtained in step (1) are sequentially added dropwise to the berberine bisulfate solution obtained in step (2) to obtain a composite solution, wherein the concentration of berberine bisulfate in the composite solution is 0.6% (w / v), the concentration of tannic acid is 0.6% (w / v), and the concentration of dipotassium glycyrrhizinate is 0.3% (w / v), 0.6% (w / v), and 1.2% (w / v), respectively. The pH is then adjusted to 5, and the mixture is stirred at a speed of 100 rpm for 120 min to obtain water-soluble aggregation-induced luminescence glycyrrhizic acid nanoparticles. The nanoparticles obtained in this example are named nanoparticle 7, nanoparticle 8, and nanoparticle 9 in order from low to high concentrations of dipotassium glycyrrhizinate.

[0064] Example 4

[0065] (1) Trisodium glycyrrhizinate powder was uniformly dispersed in deionized water, and stirred at 1000 rpm for 30 min in a water bath (85° C.) to obtain a trisodium glycyrrhizinate solution with a concentration of 2% (w / v).

[0066] (2) The 13-hydroxy-8-oxoberberine powder was evenly dispersed in deionized water, and stirred at 500 rpm for 30 min at 40° C. to obtain a 13-hydroxy-8-oxoberberine solution with a concentration of 1.5% (w / v).

[0067] (3) Dissolve tannic acid powder in deionized water and stir at 100 rpm for 30 min at 30° C. to obtain a tannic acid solution with a concentration of 1.5% (w / v).

[0068] (4) The trisodium glycyrrhizinate solution obtained in step (1) and the 13-hydroxy-8-oxoberberine solution obtained in step (2) were sequentially added dropwise to the tannic acid solution obtained in step (3) to obtain a composite solution, wherein the concentration of trisodium glycyrrhizinate in the composite solution was 0.8% (w / v), the concentration of 13-hydroxy-8-oxoberberine was 0.4% (w / v), and the concentration of tannic acid was 0.4% (w / v), respectively. The pH was then adjusted to 3.5, 4, 4.5 and 5, and the mixture was stirred at 400 rpm for 90 min to obtain water-soluble aggregation-induced luminescence glycyrrhizic acid nanoparticles. The nanoparticles obtained in this example were named nanoparticle 10, nanoparticle 11 and nanoparticle 12 in order from pH 3.5 to 5.

[0069] Example 5

[0070] (1) Monopotassium glycyrrhizinate powder was uniformly dispersed in deionized water, and stirred at 800 rpm for 20 min in a water bath (70° C.) to obtain a monopotassium glycyrrhizinate solution with a concentration of 0.4% (w / v).

[0071] (2) The berberine chloride dihydrate powder was uniformly dispersed in deionized water, and stirred at 800 rpm for 10 min at 30° C. to obtain a berberine chloride dihydrate solution with a concentration of 1% (w / v).

[0072] (3) Dissolve tannic acid powder in deionized water and stir at 800 rpm for 5 min at 60° C. to obtain a tannic acid solution with a concentration of 0.4% (w / v).

[0073] (4) The potassium glycyrrhizic acid solution, the berberine chloride dihydrate solution and the tannic acid solution were mixed in a certain order to obtain a composite solution, wherein the concentration of potassium glycyrrhizic acid in the composite solution was 0.1% (w / v), the concentration of berberine chloride dihydrate was 0.05% (w / v), and the concentration of tannic acid was 0.1% (w / v), and then the pH was adjusted to 3.5, and the mixture was stirred at a speed of 500 rpm for 60 min to obtain water-soluble aggregation-induced luminescence glycyrrhizic acid nanoparticles. The nanoparticles prepared in this example are named as shown in Table 1 below:

[0074] Table 1

[0075]

[0076]

[0077] Example 6

[0078] (1) Disperse potassium glycyrrhizinate powder evenly in deionized water, and stir at 1000 rpm for 30 min in a water bath (85° C.) to obtain a potassium glycyrrhizinate solution with a concentration of 4% (w / v).

[0079] (2) The berberine hydrochloride powder was evenly dispersed in deionized water, and stirred at 500 rpm for 30 min at 60° C. to obtain a berberine hydrochloride solution with a concentration of 2% (w / v).

[0080] (3) Dissolve tannic acid powder in deionized water and stir at 300 rpm for 30 min at 40° C. to obtain a tannic acid solution with a concentration of 2% (w / v).

[0081] (4) The potassium glycyrrhizic acid solution obtained in step (1) and the berberine hydrochloride solution obtained in step (2) were sequentially added dropwise to the tannic acid solution obtained in step (3) to obtain a composite solution, wherein the concentration of potassium glycyrrhizic acid in the composite solution was 1% (w / v), the concentration of berberine hydrochloride was 0.5% (w / v), and the concentration of tannic acid was 1% (w / v), and then the pH was adjusted to 3.5, and the mixture was stirred at 400 rpm for 120 min to obtain water-soluble aggregation-induced luminescence glycyrrhizic acid nanoparticles. The nanoparticles obtained in this example are named nanoparticles 19, and the pH of nanoparticles 19 is then adjusted to 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, and 7.5, respectively.

[0082] Comparative Example 1

[0083] Dipotassium glycyrrhizinate powder was evenly dispersed in deionized water, and stirred at 500 rpm for 5 min in a water bath (60° C.), and the pH was adjusted to 3.5 to obtain a dipotassium glycyrrhizinate solution with a concentration of 0.4% (w / v). The sample prepared in this example was named Solution 1.

[0084] Comparative Example 2

[0085] The berberine sulfate powder was evenly dispersed in deionized water, and stirred at 500 rpm for 30 min at 20° C., and the pH was adjusted to 4 to obtain a berberine sulfate solution with a concentration of 0.4% (w / v). The sample prepared in this example was named Solution 2.

[0086] Comparative Example 3

[0087] Tannic acid powder was uniformly dispersed in deionized water, and stirred at 500 rpm for 10 min at 20° C., and the pH was adjusted to 4.5 to obtain a tannic acid solution with a concentration of 0.4% (w / v). The sample prepared in this example was named Solution 3.

[0088] Comparative Example 4

[0089] (1) Disperse monopotassium glycyrrhizinate powder evenly in deionized water, and stir at 500 rpm for 20 min in a water bath (60° C.) to obtain a monopotassium glycyrrhizinate solution with a concentration of 2% (w / v).

[0090] (2) The berberine bisulfate powder was evenly dispersed in deionized water, and stirred at 40° C. and 600 rpm for 20 min to obtain a berberine bisulfate solution with a concentration of 1% (w / v).

[0091] (3) The berberine bisulfate solution obtained in step (2) was added dropwise to the monopotassium glycyrrhizic acid solution obtained in step (1), the pH was adjusted to 4, and the mixture was stirred at 400 rpm for 120 min to obtain a glycyrrhizic acid-berberine composite solution, wherein the concentration of monopotassium glycyrrhizic acid in the composite solution was 0.5% (w / v) and the concentration of berberine hydrochloride was 0.5% (w / v). Composite solution 1 obtained in this example.

[0092] Comparative Example 5

[0093] (1) Dipotassium glycyrrhizinate powder was uniformly dispersed in deionized water, and stirred at 600 rpm for 10 min in a water bath (70° C.) to obtain a dipotassium glycyrrhizinate solution with a concentration of 1% (w / v).

[0094] (2) The tannic acid powder was uniformly dispersed in deionized water and stirred at 100 rpm for 60 min to obtain a tannic acid solution with a concentration of 1% (w / v).

[0095] (3) Add the tannic acid solution obtained in step (2) dropwise to the dipotassium glycyrrhizinate solution obtained in step (1), adjust the pH to 4.5, and stir at 600 rpm for 30 min to obtain a glycyrrhizic acid-tannic acid composite solution, so that the concentration of dipotassium glycyrrhizinate in the composite solution is 0.5% (w / v), and the concentration of tannic acid is 0.5% (w / v). The nanoparticles obtained in this example are named composite solution 2.

[0096] Comparative Example 6

[0097] (1) Berberine chloride dihydrate powder was uniformly dispersed in deionized water, and stirred at 500 rpm for 30 min at 20° C. to obtain a berberine chloride dihydrate solution with a concentration of 1% (w / v).

[0098] (2) The tannic acid powder was uniformly dispersed in deionized water and stirred at 600 rpm for 10 min to obtain a tannic acid solution with a concentration of 1% (w / v).

[0099] (3) Add the tannic acid solution obtained in step (2) dropwise to the berberine chloride dihydrate solution obtained in step (1), adjust the pH to 4.5, and stir at 800 rpm for 90 min to obtain a berberine-tannic acid composite solution, so that the concentration of the berberine chloride dihydrate solution in the composite solution is 0.5% (w / v), and the concentration of tannic acid is 0.5% (w / v). The nanoparticles obtained in this example are named composite solution 3.

[0100] Performance Testing:

[0101] (1) Sample stability and particle size analysis:

[0102] The particle size and potential of the nanoparticles were studied using a Zetasizer Nano ZS particle size potential analyzer, and three parallel measurements were performed for each sample.

[0103] Table 2 Particle size, potential, state, stability and fluorescence phenomenon of samples under UV light

[0104]

[0105] The present invention takes Examples 1-4 and Comparative Examples 4-6 as examples to measure the particle size and potential of uniformly dispersed samples, and observe their stability and appearance. The particle size, potential, state, stability and fluorescence phenomenon under ultraviolet light of each sample are shown in Table 2. Nanoparticles 1-3, nanoparticles 5-8 and composite solution 1 all showed obvious yellow precipitation after standing for 3 hours, indicating that the preparation conditions could not produce stable nanoparticles. Composite solution 2 was white and transparent due to the absence of berberine or berberine derivatives, and no fluorescence phenomenon was observed under ultraviolet light. Weak fluorescence can be observed in composite solution 3, which indicates that the weak interaction between berberine and tannic acid can produce a weak aggregation-induced emission effect. The particle size of nanoparticle 4 is 303.0±33.9nm, and the potential is -31.1±0.2mV; the particle size of nanoparticle 9 is 393.5±64.5nm, and the potential is -29.3±0.3mV. The absolute value of the potential of nanoparticle 4 is greater than 30 mV, indicating that the electrostatic repulsion between the particles is strong enough to prevent them from aggregating or precipitating. The absolute value of the potential of nanoparticle 9 is between 20 mV and 30 mV, and the particles are in a relatively stable state. This shows that relatively stable AIE nanoparticles can be formed under these two concentration ratios.

[0106] The particle sizes of the nanoparticles 10-12 in Example 4 are all between 300-400 nm, the absolute values ​​of the potentials are all greater than 30 mV, the solution is evenly dispersed without precipitation, and bright green fluorescence appears under ultraviolet light, indicating that the conditions in Example 4 can successfully prepare water-soluble aggregation-induced luminescence glycyrrhizic acid nanoparticles.

[0107] (2) Fluorescence properties of nanoparticles

[0108] The fluorescence intensity of the nanoparticles was tested using a fluorescence spectrophotometer, with an excitation voltage of 700 V, an excitation wavelength of 405 nm, a slit width of 5 nm, a scanning range of 450-675 nm, and a reaction time of 0.1 s.

[0109] The present invention takes solution 1-3, composite solution 2-3, nanoparticle 4 in Example 2 and nanoparticle 9 in Example 3 as examples, and measures their fluorescence emission spectra at an excitation wavelength of 405 nm. The fluorescence spectra of solution 1-3, composite solution 2-3, nanoparticle 4 in Example 2 and nanoparticle 9 in Example 3 are as follows: Figure 2As shown. In solutions 1-3, nanoparticles cannot be prepared from dipotassium glycyrrhizinate alone, berberine sulfate alone or tannic acid alone. However, solution 2 has weak fluorescence in aqueous solution, which is caused by the intramolecular vibration behavior of berberine in water. The fluorescence intensity of composite solution 3 is slightly improved, indicating that the weak interaction between berberine and tannic acid can produce a weak aggregation-induced emission effect. Relative to composite solution 3, the fluorescence intensity of nanoparticles 4 in Example 2 and nanoparticles 9 in Example 3 is greatly improved, indicating that the addition of glycyrrhizic acid can significantly enhance the fluorescence emission of nanoparticles. This may be due to the non-covalent interaction between glycyrrhizic acid-berberine-tannic acid, which enhances the steric hindrance of berberine, thereby inhibiting the non-radiative transition of molecules in the system and producing a significant AIE effect.

[0110] Taking the water-soluble nanoparticles 13-18 in Example 5 as an example, the effect of different mixing orders on the fluorescence intensity of the nanoparticles was investigated. The fluorescence spectra of the nanoparticles 13-18 in Example 5 are shown in FIG. Figure 3 At the same concentration and pH, the fluorescence intensity of the nanoparticles prepared in different mixing orders was different (the fluorescence intensity from strong to weak was: nanoparticle 15> nanoparticle 14> nanoparticle 17> nanoparticle 13> nanoparticle 16> nanoparticle 18), indicating that the mixing order of glycyrrhizic acid, berberine and polyphenol solution was an important factor affecting the fluorescence intensity of glycyrrhizic acid nanoparticles.

[0111] (3) pH fluorescence responsiveness of nanoparticles

[0112] The test method uses a fluorescence spectrophotometer to test the fluorescence intensity of the nanoparticles. The excitation voltage is 700V, the excitation wavelength is 405nm, the slit width is 5nm, the emission wavelength is 540nm, and the reaction time is 0.1s.

[0113] Taking the nanoparticle 19 in Example 6 as an example, the effect of pH on the fluorescence characteristics of the nanoparticles was investigated. The pH-responsive fluorescence intensity of the nanoparticle 19 in Example 6 is shown in FIG. Figure 4 As shown. When the pH gradually increases from 2 to 7.5, the fluorescence intensity of the nanoparticles 19 in Example 6 first increases and then decreases, presenting a peak shape, and reaches the highest at a pH of 3.5. Under acidic conditions, the fluorescence intensity of the nanoparticles 19 in Example 6 is maintained at a high level. Although the fluorescence intensity of the nanoparticles is greatly reduced under neutral conditions, a certain fluorescence intensity is still maintained. This may be because although the nanoparticles aggregate under acidic conditions, their structure does not disintegrate, and the closer to neutral conditions, the looser the structure of the nanoparticles. The results show that within the pH range of 2-7.5, the nanoparticles 19 in Example 6 have fluorescent properties and exhibit pH fluorescence responsiveness.

[0114] (4) Fluorescence characteristics of nanoparticles during gastrointestinal digestion

[0115] Preheat the sample, simulated saliva (SSF), simulated gastric fluid (SGF), and simulated intestinal fluid (SIF) in a 37°C water bath. Mix equal volumes of pre-ingestion sample (5 mL) and SSF (pH 7.0) and adjust the pH to 7.0. Add α-salivary amylase to the mixture to reach 75 U / mL, add CaCl2 to reach 1.5 mM, and mix and shake. After 2 minutes, mix equal volumes of simulated oral fluid and SGF (pH 3.0) and adjust the pH to 3.0. Add pepsin to the mixture to reach 2000 U / mL and add CaCl2 to reach 0.15 mM. Incubate in a 37°C water bath for 2 hours, and collect equal amounts of gastric digesta every half an hour. Afterwards, mix equal volumes of simulated gastric digesta and SIF (pH 7.0) and adjust the pH to 7.0. Add bile salts to the mixture to reach 10 mM, add trypsin to reach 100 U / mL, and add CaCl2 to reach 0.6 mM. The cells were cultured at 37°C and 100 rpm for 2 h, and equal amounts of intestinal digesta were collected every half hour.

[0116] Taking the nanoparticle 9 in Example 3 as an example, the effect of gastrointestinal digestion on the fluorescence characteristics of the nanoparticles was explored. The fluorescence intensity of the nanoparticle 9 in Example 3 during gastrointestinal digestion is shown in FIG. Figure 5 As shown. In the gastric digestion stage, the nanoparticles 9 in Example 3 can maintain a high fluorescence intensity, but the fluorescence intensity begins to decrease after 2 hours of intestinal digestion, which may be related to the loose structure of the particles in a neutral environment. Figure 5 In comparison, it was found that the fluorescence intensity of the nanoparticles during intestinal digestion was greater than that of the samples under neutral conditions. This may be due to the addition of a large amount of inorganic salts in the environment simulating gastrointestinal digestion, which increased the ionic strength of the solution and the N + The electrostatic interactions involved will increase with the increase of ionic strength, so the fluorescence intensity of nanoparticles is higher during intestinal digestion. In short, nanoparticles can maintain good fluorescence properties during gastrointestinal digestion.

[0117] (5) Cell imaging test:

[0118] 1×10 cells were cultured per well in a laser confocal microplate. 5 Caco-2 cells were cultured at 37°C and 5% CO2 for 24 hours to allow the cells to adhere to the wall. Then the sample (1000 μg / mL) was added and incubated at 37°C for 3 hours. After washing with DPBS three times, DAPI (10 μg / mL) was added and stained at 37°C in the dark for 10 minutes, and then washed with DPBS three times, and the cell uptake was observed using a fluorescence microscope.

[0119] The present invention takes the nanoparticle 4 in Example 2 as an example to observe the cellular uptake of the nanoparticle by Caco-2 cells. The Caco-2 cell imaging image of the nanoparticle 4 in Example 2 is as follows: Figure 6 DAPI was used to specifically label the nucleus of Caco-2 cells. Figure 6 In A, it can be clearly observed that the cell nucleus emits bright blue fluorescence, indicating that DAPI can be localized in the cell nucleus of living cells. After intervening Caco-2 cells with nanoparticles 4 for 3 hours, it was found that Figure 6 The cells in B emit green fluorescence, indicating that Caco-2 cells successfully take up glycyrrhizic acid nanoparticles with aggregation-induced luminescence properties into the cytoplasm. Figure 6 In C, it can be clearly observed that the blue fluorescence of the cell nucleus and the green fluorescence of the cytoplasm overlap, further indicating that nanoparticle 4 has a specific targeting effect on the Caco-2 cytoplasm.

[0120] In summary, the water-soluble AIE nanoparticles prepared by the present invention have high biocompatibility, small particle size (300-400nm), good water solubility, aggregation-induced emission characteristics and pH fluorescence responsiveness, and still show fluorescence characteristics after gastrointestinal digestion. The preparation process of the fluorescent nanoparticles is green and mild, and can be used for efficient cell imaging and gastrointestinal fluorescence tracing, and has potential practical application value in the fields of functional food and biomedicine.

[0121] The above implementation is only a preferred implementation mode of the present invention and is only used to explain the present invention rather than to limit the present invention. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention are included in the protection scope of the present invention.

Claims

1. A method for preparing aggregation-induced luminescence glycyrrhizic acid nanoparticles, characterized in that: The following steps are involved: The glycyrrhizic acid or glycyrrhizic acid derivative solution, berberine or berberine derivative solution and tannic acid solution are mixed to obtain a composite solution, the pH value of the composite solution is adjusted to acidic, and the composite solution is stirred to obtain aggregation-induced luminescent glycyrrhizic acid nanoparticles.

2. The preparation method according to claim 1, characterized in that: The mass ratio of glycyrrhizic acid or glycyrrhizic acid derivatives to berberine or berberine derivatives in the composite solution is 0.5-2:

1.

3. The preparation method according to claim 1, characterized in that: The mass ratio of tannic acid to berberine or berberine derivative in the composite solution is 0.5-2:

1.

4. The preparation method according to claim 1, characterized in that: In the composite solution, the mass volume concentration of glycyrrhizic acid or glycyrrhizic acid derivatives is 0.01-2%, g / mL; the mass volume concentration of berberine or berberine derivatives is 0.01-2%, g / mL; and the mass volume concentration of tannic acid is 0.01-2%, g / mL.

5. The preparation method according to claim 1, characterized in that: The mass ratio of glycyrrhizic acid or glycyrrhizic acid derivatives to berberine or berberine derivatives in the composite solution is 1.8-2.2:1; The mass ratio of tannic acid to berberine or berberine derivative in the composite solution is 1-2:

1.

6. The preparation method according to claim 1, characterized in that: The pH value is 3.5-5; The stirring time is 30-120 min, and the stirring speed is 100-1000 rpm; The mixing order includes sequentially adding tannic acid solution and berberine or berberine derivative solution to glycyrrhizic acid or glycyrrhizic acid derivative solution, sequentially adding berberine or berberine derivative solution and tannic acid solution to glycyrrhizic acid or glycyrrhizic acid derivative solution, sequentially adding glycyrrhizic acid or glycyrrhizic acid derivative solution and tannic acid solution to berberine or berberine derivative solution, sequentially adding tannic acid solution and glycyrrhizic acid or glycyrrhizic acid derivative solution to berberine or berberine derivative solution, sequentially adding berberine or berberine derivative solution and glycyrrhizic acid or glycyrrhizic acid derivative solution to tannic acid solution, and sequentially adding glycyrrhizic acid or glycyrrhizic acid derivative solution and berberine or berberine derivative solution to tannic acid solution.

7. The preparation method according to claim 1, characterized in that: (1) The solution of glycyrrhizic acid or a glycyrrhizic acid derivative is prepared as follows: Evenly dispersing glycyrrhizic acid or a glycyrrhizic acid derivative in water, and heating and stirring to obtain a solution of glycyrrhizic acid or a glycyrrhizic acid derivative; (2) The preparation of berberine or berberine derivative solution is as follows: Dispersing berberine or a berberine derivative in water, and heating and stirring to obtain a berberine or a berberine derivative solution; (3) The tannic acid solution is prepared as follows: Tannic acid is dispersed in water and heated and stirred to obtain a tannic acid solution.

8. The preparation method according to claim 7, characterized in that: The glycyrrhizic acid derivatives described in step (1) include one or more of ammonium glycyrrhizinate, monopotassium glycyrrhizinate, dipotassium glycyrrhizinate, and trisodium glycyrrhizinate; the mass volume concentration of the glycyrrhizic acid or glycyrrhizic acid derivative solution described in step (1) is 0.4-4%, g / mL; The heating and stirring temperature in step (1) is 60-90° C., the heating and stirring time is 5-30 min, and the heating and stirring speed is 100-1000 rpm; The berberine derivative described in step (2) includes one or more of berberine hydrochloride, berberine sulfate, berberine hydrogen sulfate, berberine chloride dihydrate, and 13-hydroxy-8-oxoberberine; the mass volume concentration of the berberine or berberine derivative solution described in step (2) is 0.4-2%, g / mL; The heating and stirring temperature in step (2) is 20-60° C., the heating and stirring time is 5-30 min, and the heating and stirring speed is 100-1000 rpm; The mass volume concentration of the tannic acid solution in step (3) is 0.4-2%, g / mL; The heating and stirring temperature in step (3) is 20-60° C., the heating and stirring time is 5-30 min, and the heating and stirring speed is 100-1000 rpm.

9. Aggregation-induced luminescence glycyrrhizic acid nanoparticles prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the aggregation-induced luminescence glycyrrhizic acid nanoparticles according to claim 9 in the preparation of imaging agents, the preparation of tracing agents, and as drug carriers.

Citation Information

Patent Citations

  • A water-soluble aggregation-induced emission nanoparticle, its preparation method and application

    CN113788795B

  • Water-soluble aggregation-induced emission photosensitizer and preparation method thereof

    CN114656502A

Cited By

  • Aggregation-induced emission material as well as preparation method and application thereof

    CN121249353A

  • An aggregation-induced emission material, a preparation method and application thereof

    CN121249353B